Strategi Berdagang Pedagang Kaki Lima Di Dracik Kampus Kabupaten Batang (Tinjauan Sosiologi Ekonomi) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
This study adopted a descriptive qualitative methodology, using in-depth interviews and direct observation to perform its research. Food and drink, home appliances, carpentry equipment, stationery, photocopiers, and other types of items are among the various types of goods that vendors in the Dracik Campus Field may sell. From conversations with traders at the Dracik Kampus Field, it was learned which area was the most advantageous for selling. The Dracik Kampus Field Traders' marketing plan involves leveraging social media sites like Facebook and loudspeakers to assist in-person promotions made by the traders. Because there are three schools nearby, it is suggested that the vendors set up shop in the morning and evening to avoid the heavy traffic that occurs when people are leaving and arriving from school.